Предмет: Алгебра,
автор: Erasyl345
Помагите пожалуйста!
Приложения:
![](https://files.topotvet.com/i/7af/7af1014c479c3ccaff778159fa61157d.jpg)
Ответы
Автор ответа:
1
Ответ:
2
Объяснение:
(х-2)(х+2)-(х-3)^2=-1
х^2-4-(х^2-6х+9)=-1
х^2-4-х^2+6х-9=-1
-4+6х-9=-1
6х-13=-1
6х=-1+13
6х=12
х=12:6
х=2
Похожие вопросы
Предмет: Английский язык,
автор: kkkkiiiii
Предмет: Русский язык,
автор: diasdosumovmailru
Предмет: Русский язык,
автор: марго881
Предмет: История,
автор: Anna27072001
Предмет: Математика,
автор: пуговечка